Hierarchical Porous Nanostructures of Manganese(III) Oxyhydroxide for All‐Solid‐State Flexible Supercapacitors. Issue 11 (16th August 2016) - Dai, Shuge; Liu, Jianlin; Wang, Chuanshen; Wang, Xue; Xi, Yi; Wei, Dapeng; Hu, Chenguo
Abstract: A three‐dimensional porous MnOOH hierarchical nanostructure grown on flexible carbon fiber fabric is successfully synthesized by a facile hydrothermal method. Monoclinic MnOOH has a crystalline structure layered in the [010] direction. The layered structure facilitates intercalation/deintercalation of Li + into the interlayer space as well as the adsorption/desorption of Li + onto the surface of each layer during fast charging/discharging process. This porous hierarchical structure provides many electroactive sites and efficient paths for ion transport. When used as flexible and lightweight electrodes for supercapacitors, the porous MnOOH electrode manifests good electrochemical performance with a high capacitance of 160 F g −1 at a current density of 0.2 mA cm −2, a high energy density of 14 Wh kg −1 at a power density of 162 W kg −1, and great cycling stability. Moreover, the application for the low‐cost and highly flexible supercapacitors in powering light‐emitting diodes (LEDs) highlights its enormous commercial potential in next‐generation energy storage systems. Abstract : Mn‐O‐O‐H, that spells… : A porous hierarchical nanostructure of manganese(III) oxyhydroxide (MnOOH) is successfully grown on a flexible carbon fiber fabric (CFF) by a facile hydrothermal method. The porous hierarchical structure offers a large surface area, an abundance of electroactive sites, and efficient ion transport paths. These features greatly improve the electrochemical performance of MnOOH supercapacitors (SCs).